2021
DOI: 10.15766/mep_2374-8265.11163
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Communication Skills Workshop Using Standardized Patients for Senior Medical Students

Abstract: Introduction: Medical students often lack training in advanced communication skills encompassing emotionally fraught situations and those in which an intense emotional response is expected. Such skills are required for clinical situations encountered during residency. We created and evaluated an advanced communication skills workshop (ACSW) using standardized patients for senior medical students. The workshop emphasized communication skills for four scenarios-strong emotion, goals of care, medical error, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The evolution of modern medicine from a purely biomedical model to a "biopsychosocial" medical approach underscores the importance of empathetic patient interaction and effective communication. As part of resident training, the capacity to empathize with patients and communicate in an advanced way is a pivotal assessment criterion [20] . Exceptional pediatric residents need not excel in all areas but should specialize in clinical practice, scientific research, or communication skills.…”
Section: Table 3 Indicator Improvement Formentioning
confidence: 99%
“…The evolution of modern medicine from a purely biomedical model to a "biopsychosocial" medical approach underscores the importance of empathetic patient interaction and effective communication. As part of resident training, the capacity to empathize with patients and communicate in an advanced way is a pivotal assessment criterion [20] . Exceptional pediatric residents need not excel in all areas but should specialize in clinical practice, scientific research, or communication skills.…”
Section: Table 3 Indicator Improvement Formentioning
confidence: 99%
“…Thus, a wide range of approaches, frameworks, and curriculums have been developed to help health care professionals at any career stage learn a range of communication strategies. 6 – 13 For instance, surgery residents who took an 8-module training that covered empathic communication, end-of-life conversations, bad news delivery, and medical error disclosure reported positive learning experiences and increased confidence—results that correlated with patient perceptions of improved surgeon communication. 13 And a randomized trial that evaluated a coaching intervention in which coaches taught 5 different communication skills to cardiologists revealed that those who received coaching had improved their ability to express empathy and elicit questions from patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of participants, 62% reported that medical school training had prepared them not at all or minimally for these conversations. 9 Despite this recognized challenge in communication, most existing interventions aim to improve communication skills [10][11][12][13] or reasoning under uncertainty, 14,15 but there are few interventions aimed at educating medical students on how to communicate uncertainty to patients or to tolerate uncertainty.…”
Section: Introductionmentioning
confidence: 99%